O século de ferro: o discurso sobre a guerra em “O Príncipe” de Maquiavel e “A educação de um príncipe cristão” de Erasmo (1494-1518) - Souza, Éder Nunes (2022)
At the beginning of the Modern Age, in the 15th and 16th centuries, Europe went through a period of intense transformation. The end of the 100 Years' War (1337 - 1453), the conclusion of the Spanish Reconquest by conquering the Muslim kingdom of Granada (1492), the Maritime Expansion, the discovery of territories and peoples unknown to Europeans in addition to the Ottoman-Turkish conquest of Constantinople (1453) and its advance through the Mediterranean and Eastern Europe change the political scenario in Europe, which is marked in this period by the decadence of the medieval Christian republic and the continuation of the succession of States. Erasmus of Rotterdam (1466 - 1536) and Machiavelli (1469 - 1527) were coeval and shared political and intellectual contexts. Italy has been transformed since the main political conflict and the Valois 1 little scene49, the new armaments period, the mortality and the violence hitherto usual makes the thought of having as a degree of concern the war, and questioning about which it is his concept, if war can be just and what should be the appropriate posture of a ruler in the face of the possibility of occurrence of armed conflicts. The central book of this dissertation is to understand how Machiavelli and Erasmus established the concept of objective warfare in their works The Prince (1513) and The Education of a Christian Prince (1516) in their prince’s mirrors, the literary style to which the texts belong. studied. The mirrors aim not only to advise the leaders, they serve as a mechanism for intervention in the political debate and aim to be action guides in the decision-making of monarchs